2022
DOI: 10.1016/j.cegh.2022.100969
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and risk factors for the development of drug related problems among rheumatoid arthritis patients

Abstract: Background: Rheumatoid arthritis (RA) patients are at high risk for development of drug related problems (DRPs) due to multiple drug use. This study aimed to estimate the frequency and risk factors for the development of drug related problems among RA patients in Indian setting. Methods: A prospective cohort study was carried out for twenty-two months in a tertiary care teaching hospital. Patients who met study eligibility criteria were randomised either into intervention or usual care group. All the patients'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Although interview two resulted in a different top three of most common types of unique DRPs when compared to interviews one, three and four, the top three subtypes per interview remained constant. This study quantified relatively high numbers of DRPs (median of 5 (IQR 3–9) unique DRPs per patient) when compared to previous studies, which reported 1–2 DRPs per patient in rheumatic diseases populations [ 8 , 9 , 21 ]. Main DRPs in patients with rheumatic diseases identified in other (pro- and retrospective) studies include treatment safety, treatment effectiveness, adverse reactions and drug-drug interactions.…”
Section: Discussionmentioning
confidence: 93%
“…Although interview two resulted in a different top three of most common types of unique DRPs when compared to interviews one, three and four, the top three subtypes per interview remained constant. This study quantified relatively high numbers of DRPs (median of 5 (IQR 3–9) unique DRPs per patient) when compared to previous studies, which reported 1–2 DRPs per patient in rheumatic diseases populations [ 8 , 9 , 21 ]. Main DRPs in patients with rheumatic diseases identified in other (pro- and retrospective) studies include treatment safety, treatment effectiveness, adverse reactions and drug-drug interactions.…”
Section: Discussionmentioning
confidence: 93%